1995
DOI: 10.1128/jb.177.12.3472-3478.1995
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular PI-type proteinase of Lactococcus lactis hydrolyzes beta-casein into more than one hundred different oligopeptides

Abstract: The peptides released from ␤-casein by the action of P I -type proteinase (PrtP) from Lactococcus lactis subsp. cremoris Wg2 have been identified by on-line coupling of liquid chromatography to mass spectrometry. After 24 h of incubation of ␤-casein with purified PrtP, a stable mixture of peptides was obtained. The trifluoroacetic acid-soluble peptides of this ␤-casein hydrolysate were fractionated by high-performance liquid chromatography and introduced into the liquid chromatography-ion spray mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 44 publications
6
108
0
4
Order By: Relevance
“…The central role of the oligopeptide transport system in the proteolytic pathway of L. lactis has recently been demonstrated (10). The need for di-and tripeptide transport systems in L. lactis is less apparent, since di-and tripeptides are not released from ␤-casein by the proteinase PrtP (9). However, growth of L. lactis in medium containing a mixture of caseins requires the presence of a functional di-and tripeptide transport system(s) (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central role of the oligopeptide transport system in the proteolytic pathway of L. lactis has recently been demonstrated (10). The need for di-and tripeptide transport systems in L. lactis is less apparent, since di-and tripeptides are not released from ␤-casein by the proteinase PrtP (9). However, growth of L. lactis in medium containing a mixture of caseins requires the presence of a functional di-and tripeptide transport system(s) (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, growth of L. lactis in medium containing a mixture of caseins requires the presence of a functional di-and tripeptide transport system(s) (26). Although small peptides have not been detected in the degradation of ␤-casein by PrtP (9), it has been suggested that at least one essential amino acid is taken up in the form of a di-or a tripeptide which could be released from casein species other than the ␤ form (e.g., -casein) (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…C'est également la caséine utilisée préfé-rentiellement lors de la croissance de L lacfis (Exterkate et de Veer, 1987). De ce fait, de nombreuses études ont porté sur l'identification des peptides libérés après hydrolyse de la caséine~par une protéase de paroi purifiée (Visser et al, 1988(Visser et al, , 1991Monnet et al, 1989 ;Reid et al, 1991 (Juillard et al, 1995b a From Tan et al, 1993. approche a prouvé que l'hydrolyse de la caséine p par une protéase de paroi génère un nombre de peptides beaucoup plus important que ce que l'on pensait jusqu'alors.…”
Section: Utilisation Des Caséinesunclassified
“…Enfin, la croissance dans du lait de ces différents mutants corrobore les résultats des expériences de transport. Le niveau cellu- Juillard et al, 1995b . laire atteint par une souche Prtt incapable de transloquer les oligopeptides représente moins de 5 % de celui atteint par la souche sauvage .…”
Section: Utilisation Des Caséinesunclassified
“…lactocepin, which mainly releases peptides of large molecular mass from caseins (Juillard et al, 1995b;Kunji et al, 1996).…”
Section: Introductionmentioning
confidence: 99%